Effect of repeat catheter ablation vs. antiarrhythmic drug therapy among patients with recurrent atrial tachycardia/atrial fibrillation after atrial fibrillation catheter ablation: data from CHINA-AF registry. Issue 2 (26th September 2022) - Zhou, Lu; He, Liu; Wang, Wei; Li, Changyi; Li, Songnan; Tang, Ribo; Sang, Caihua; Liu, Nian; Jiang, Chenxi; Yu, Ronghui; Long, Deyong; Du, Xin; et al.
Abstract: Aims: Although several studies have proved that repeat catheter ablation is beneficial to recurrent atrial tachycardia (AT)/atrial fibrillation (AF) after AF catheter ablation, the hard endpoints of the effect of catheter ablation on recurrent AT/AF patients after AF catheter ablation remains unclear. Our study aims to compare the effect of catheter ablation and drug therapy on recurrent AT/AF patients after AF catheter ablation. Methods and results: Four thousand nine hundred and thirteen consecutive patients with recurrent AT/AF after catheter ablation from the China-AF registry were enrolled. The patients were divided into two study groups: the repeat catheter ablation group and the medical therapy group. The primary endpoint is a composite of cardiovascular mortality or ischaemic stroke or major bleeding events. Secondary endpoints were each component of the primary endpoints and AF recurrence rate. Landmark analysis and Cox regression were used in the statistical analysis. We chose landmark 36 months as the primary landmark date. Over a median follow-up period of 40 ± 24 months, 4913 patients were divided into either the repeat ablation group or the medical therapy group. The cumulative incidence of the composite primary outcome was significantly lower in the repeat ablation group than the medical therapy group (adjusted hazard ratio = 0.56; 95% confidence interval: 0.35–0.89; P = 0.015) of landmark 36 months (2359 patients were included in medical therapy group and 704 patients were included in repeat ablation group at landmark 36 months). However, all secondary endpoints were not statistically different in the two groups, including cardiovascular mortality, ischaemic stroke, major bleeding events, and AF recurrence rate. Conclusion: Based on this research, in recurrent AT/AF patients after a catheter ablation procedure, compared with medical therapy, repeat catheter ablation may significantly reduce the risk of the endpoint of composite cardiovascular mortality, ischaemic stroke, and major bleeding events.